A obra coreográfica como experiência poética e educativa: uma abordagem fenomenológica - Viana, Ana Cláudia Albano (2020)
In our thesis, we state the choreographic piece as a poetic and educational experience. We consider the choreographic piece as a visible letter that writes and install itself in the corporeity involved through its movements and sensations’ poetry. Its operation of expression allows us to the perception of the human symbolic potentiality, in order to educate us to the sensible and creation of meanings. In the research, we had the following purposes: 1) to do aesthetic appreciation of the pieces, in their poetics, images and expressivities; 2) establish phenomenologists relations between body, dance images and intercorporeity; and 3) point out perspectives for education’s comprehension through intercorporeity, choreographic piece as poetic and educational experience and body awareness. Our research’s theorical and methodological reference is the Meleau-Ponty’s phenomenology and our main interlocutors are Merleau-Ponty (1945/1999; 1969/2002; 1960/1991; 1964/2005), Paul Valéry (1939/2015), and in the relation between main interlocutors and the education, Nóbrega (2015; 2018b), as well as the works developed by the Estesia research group. Our analysis corpus is composed by four choreographic pieces intentionally chosen, all by the choreographer Jérôme Bel, which are Véronique Doisneau (2005), Pichet Klunchun and myself (2005), Jérôme Bel (1995) e Gala (2015). The selection criteria of the pieces and analysis made come from the signification, in the meaning of opening to new meanings’ horizons for the interlocutions among the choreographic piece and the educational phenomenon. From the phenomenological reduction and Atlas Mnémosyne (WARBURG, 2012) reference, we understand that the choreographic piece as poetic and educational experience allow us to see emblems of the world and fields of creation of other meanings, crossing of affections and of subjectivities. That occurrence is not from intellective nature, but of a perceptual nature of life. It happens for expression operation of perceptual life, kinaesthetic empathy and esthesiological body. This lead us to the comprehension of the educational phenomenon as intercorporeity, whereby, in the intercorporeal relationship, in what we lack and found on others, we perceive elements for interpretations and intelligibility relationships with the world; culture and history reinvention and strengthening of educational attitudes that value for liberty of expression; sensible listening; thought’s autonomy; creativity and consideration of the body in the educational phenomenon in the most various dimensions of life.